Modernism of Antun Gustav Matoš’s Flaneur and the Postmodern Mediaspheric Flâneurism of Branko Čegec - FRANJIĆ, Luka; Trojan, Ivan (Anafora, 2023)
This article explores the relationship between Matoš’s modern literary oeuvre and his modern media flaneurism with Branko Čegec’s postmodern intermedial literary flaneurism, by relying on the theoretical considerations of Dubravka Oraić Tolić, Krešimir Nemec, Igor Gajin and Goran Galić. The article provides an overview of the history of terms flaneur and flaneurism, with an emphasis on how they apply to Čegec’s and Matoš’s work. Since the subject in the poetry written by Čegec meanders along the signifier paths, it is necessary to determine its position in relation to the subject in Matoš’s texts. The analysis confirms that Čegec, like Matoš, is using the postmodernist apparatus, albeit with certain literary departures, to rely on intermedial sources and traces, and is thus giving a symbolic postmodern response to Matoš.